Theoretical study of the structure and stability of NbxOy, and NbxOy+ (x = 1-3; y = 2-5, 7, 8) clusters - Sambrano, JR; Andres, J.; Beltran, A.; Sensato, F.; Longo, Elson [UNESP] (Elsevier B.V., 1998)
Geometric, thermodynamic and electronic properties of cluster neutrals NbxOy and cations NbxOy+ (x = 1-3; y = 2-5, 7, 8) have been characterized theoretically. A DFT calculation using a hybrid combination of B3LYP with contracted Huzinaga basis sets. Numerical results of the relative stabilities, ionization potentials and band gaps of different clusters are in agreement with experiment. Analysis of dissociation channels supports the more stable building blocks as formed by NbO2, NbO2+ NbO3 and NbO3+ stoichiometries. The net atomic charges suggest that oxygen donor molecules can interact more favorably on central niobium atoms of cluster cations, while the interaction with oxygen acceptor molecules is more favorable on the terminal oxygen atoms of neutral clusters. A topological analysis of the electron localization function gradient field indicates that the clusters may be described as having a strong ionic interaction between Nb and O atoms. Published by Elsevier B.V. B.V.